VALUES EDUCATION IN NOVEL COUNTRY 5 TOWERMASTERPIECE A. FUADI - Sitohang, Jenti Sitohang; Rumadi, Hadi Rumadi; ', Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: Values education of country novel 5 masterpiece tower of A.Fuadi. Target of this research is to used [by] education values mendeskripsikan author in Novel Country 5 Tower. Method whichÂ  used in this research method of deskritif. Education values which there are in Novel Country 5 Tower masterpiece A. Fuadi, pursuant to result of analysis consist of four value. the Education values that is: ( a) assess education of religion represent human being obligatory viewpoint with natural God creator and content, ( b) assess education of moral that is a[n value becoming proper size measure not it human being associate with in societal life , ( c) assess education of social that is a[n emotion and awareness which relative make everlasting to a[n object, idea, or people, And ( d) liberal education value represent most storey;level Â abstraction of custom, life and take root in society mind nature Keyword: Value Education, Belleslettres And Novel.